Leveraging climate finance for gender equality and poverty reduction: A comparative study - Atmadja, S.; Liswanti, N.; Tamara, A.; Lestari, H.; Djoudi, H. (Center for International Forestry Research, 2020)
Climate finance, gender and poverty are not stand-alone, independent topics. Climate change affects all people in different ways. Climate finance can catalyze actions that can either alleviate or exacerbate gender equity and poverty. Mechanisms that fund climate action should be designed to enable, rather than hinder marginalized populations, notably women and the poor, in facing climate change. The study aims to understand climate finance for advancing gender equality and poverty reduction, by assessing different mechanisms: 1) the Village Fund (Dana Desa); 2) the Public Service Agency for Forest Development Financing Center (BLUP3H); 3) the Indonesia Climate Change Trust Fund (ICCTF); 4) the Special Allocation Fund (DAK); and 5) the Environmental Fund Management Agency (BPD-LH). The study focuses on adaptation and mitigation climate action at sub- national, which include budget items tagged in the Indonesian Climate Budget Tagging system (CBT). We assess whether climate financial flows and climate actions contribute to long-term gender transformative change and pro-poor co-benefits on the ground. The sites include the agroforestry program of BPDASHL Serayu Opak Progo in Central Java and the artesian well program in Lombok.